Self-assessed tactical skills in tennis players: Psychometric evaluation of the Tactical Skills Questionnaire in Tennis - Kolman, Nikki S.; Huijgen, Barbara C. H.; van Heuvelen, Marieke J. G.; Visscher, Chris; Elferink-Gemser, Marije T. (Frontiers in Sports and Active Living, 2022)
To our knowledge, no feasible, valid and reliable instrument exists to examine tactical skills over the course of multiple training and game situations in tennis yet. Therefore, the aim of this study was to develop and evaluate the psychometric properties of the Tactical Skills Questionnaire in Tennis (TSQT). The TSQT is a new instrument with closed-ended questions designed to examine tactical skills in tennis players. Participants were 233 competitive tennis players (age: 17.06 ± 4.74 years) competing on national or regional levels. With a principal component analysis (PCA) we identified four theoretically meaningful subscales for the 31-item TSQT: “Anticipation and positioning,” “Game intelligence and adaptability,” “Decision-making,” and “Recognizing game situations” and confirmed them with a confirmatory factor analysis (CFA) (χ2 = 527.02, df = 426, p < 0.001, CFI = 0.93, RMSEA = 0.045, SRMR = 0.079). Internal consistency was good, with Cronbach's alpha of 0.89 for the entire scale and McDonald's omega ranging from 0.69 to 0.78 for the separate subscales. A subsample of 57 players completed the TSQT twice to assess test-retest reliability. Absolute test-retest reliability of the subscales was good with no significant differences in mean scores between test and retest (p > 0.05). Relative test-retest reliability was moderate with ICC values ranging from 0.65 to 0.71. National players outperformed regional players on the subscales “Game intelligence and adaptability,” “Decision-making,” and “Recognizing game situations” (p < 0.05), and there was a trend toward significance for “Anticipation and positioning” (p = 0.07). This study supported the psychometric properties of the TSQT. Evaluating tactical skills with the TSQT provides players, coaches and other professionals with insight in players' self-assessed tactical skills over the course of multiple training and game situations. It creates the opportunity for players to reflect on their skills and detect personal development areas with their coach. We advise to use this information as input for tailor-made training programs.